Foxfire 6 shoemaking, gourd banjos, and songbows, one hundred toys and games, wooden locks, a water powered sawmill, and other affairs of just plain living - Wigginton, Eliot (Anchor Press Garden City, NY, 1980)
The latest volume in the successful series updates previous volumes and collects new crafts, reminiscences, and stories from Appalachia.
Jake Waldroop -- Gourd banjos and songbows -- Wooden locks -- Shoemaking -- Toys and games -- "Uncle John was in the crib stealing corn" -- "I did the best I could with the brain nature gave me" -- Memories of the American chestnut -- The homeplace.
Includes Index
50190
Keywords: Country life -- Georgia; Social life and customs -- Georgia; Handicraft -- Georgia